Soft Computing in Industrial Applications Algorithms, Integration, and Success Stories - Gao, X.Z.; Gaspar-Cunha, António; Köppen, Mario; Wang, Jun.; Schaefer, Gerald; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
The 14th onlineWorld Conference on Soft Computing in Industrial Applications provides a unique opportunity for soft computing researchers and practitioners to publish high quality papers and discuss research issues in detail without incurring a huge cost. The conference has established itself as a truly global event on the Internet. The quality of the conference has improved over the years. The WSC14 conference has covered new trends in soft computing to state of the art applications. The conference has also added new features such as community tools, syndication, and multimedia online presentations.
Soft Computing for Modeling, Control, and Optimization -- Optimization of Co-rotating Twin-Screw Extruders Using Pareto Local Search -- Efficient Predictive Control Algorithm Based on Fuzzy Hammerstein Models: A Case Study -- Selection of Points Inside Cutoff Radius by Scanning All Points Sorted in Memory -- Supervised Fuzzy Clustering Based Initialization of Fuzzy Partitions for Decision Tree Induction -- Fault Detection of the Tennessee Eastman Process Using Improved PCA and Neural Classifier -- New Evolutionary Methodologies -- Bare Bones Particle Swarm Applied to Parameter Estimation of Mixed Weibull Distribution -- Structural Optimization Using Harmony Search Algorithm -- Nash Dominance with Applications to Equilibrium Problems with Equilibrium Constraints -- A New Evolutionary Based Approach for Solving the Uncapacitated Multiple Allocation p-Hub Median Problem -- Soft Computing for Bioinformatics, Knowledge Management, and Data Mining -- Prediction of the hERG Potassium Channel Inhibition Potential with Use of the Artificial Neural Networks -- Michigan Style Fuzzy Classification for Gene Expression Analysis -- Feature Selection for Bankruptcy Prediction: A Multi-Objective Optimization Approach -- Dynamic Time Warping of Segmented Time Series -- Feature Selection Using Combine of Genetic Algorithm and Ant Colony Optimization -- Soft Computing for Image and Signal Processing, and Pattern Recognition -- Fully Automatic Boundary Extraction of Coronary Plaque in IVUS Image by Anisotropic Diffusion and T-S Type Fuzzy Inference -- Cost Effective 3D Localization for Low-Power WSN Based on Modified Sammon’s Stress Function with Incomplete Distance Information -- Classification of Pressure Drop Devices of Proto Type Fast Breeder Reactor through Seven Layered Feed Forward Neural Network -- Music Visualization by Means of Comb Filter and Relaxation Time According to Human Perception -- GA/SVM for Diagnosis Sleep Stages Using Non-linear and Spectral Features -- Special Session Soft Computing in Computer Graphics, Imaging, and Vision -- Prostate Boundary Detection in Ultrasound Images Based on Type-II Fuzzy Sets and Modified Fuzzy C-Means -- Distributed Multimedia Computing Using Intelligent Agents -- Object Recognition Using Simulated Evolution on Fourier Descriptors -- Special Session Soft Computing for Intelligent Control -- Embedding a KM Type Reducer for High Speed Fuzzy Controller into an FPGA -- An Application of Fuzzy Lyapunov Synthesis in the Design of Type-2 Fuzzy Logic Controllers -- Access Control and Resource Allocation for Peer-to-Peer Video Streaming Based on Fuzzy Logic -- Bio-inspired Optimization Methods of Fuzzy Logic Controllers Applied to Linear Plants -- Special Session Traffic and Transportation Systems -- An Adaptive Neuro-Fuzzy Inference System for Simulation of Pedestrians Behaviour at Unsignalized Roadway Crossings -- A Cellular Genetic Algorithm for Solving the Vehicle Routing Problem with Time Windows -- Fuzzy C-Means Based Stop Line and Crosswalk Placement at Right Turn Vehicle Exclusive Lane -- Surveys and Tutorials -- New Trends of Soft Computing Methods for Industrial and Biological Processes -- Evolutionary Multi-objective Optimisation of Business Processes -- Computational Intelligence in Speech and Audio Processing: Recent Advances.
Keywords: Computational intelligence; Artificial intelligence; Applied mathematics; Engineering mathematics; Industrial engineering; Production engineering; Computational Intelligence; Artificial Intelligence; Applications of Mathematics; Industrial and Production Engineering